Respiratory Viruses in Adults With Community-Acquired Pneumonia - Lieberman, David (Chest, 2010)
BACKGROUND: Use of nucleic acid amplification techniques has increased the identification of respiratory viruses (RVs) in adult patients with community-acquired pneumonia (CAP). The objectives of the present study were to identify RV in patients with CAP using three different sampling methods and to compare CAP virus proportions and types with two comparison groups. METHODS: The study population included 183 adult patients with CAP, 450 control subjects, and 201 patients with nonpneumonic lower respiratory tract infection (NPLRTI). Each participant was sampled by oropharyngeal swab, nasopharyngeal swab, and nasopharyngeal washing, and the samples were tested for detection of 12 RVs by multiplex TaqMan Hydrolysis probe-based real-time polymerase chain reaction (Integrated DNA Technology; Coralville, IA). RESULTS: At least one RV was identified in 58 patients with CAP (31.7%) compared with 32 (7.1%) in control subjects and 104 (51.7%) in patients with NPLRTI (P < .01 and P < .01, respectively). Coronaviruses were identified in 24 (13.1%) patients with CAP, compared with 17 (3.8%) in control subjects, and 21 (10.4%) patients with NPLRTI. Respiratory syncytial virus was identified in 13 (7.1%), four (0.9%), and seven (3.5%); rhinovirus in nine (4.9%), nine (2.0%), and 15 (7.5%); and influenza virus in eight (4.4%), two (0.4%), and 63 (31.3%) patients with CAP, control subjects, and patients with NPLRTI, respectively. CONCLUSIONS: The proportion of RV involvement in CAP is higher than previously reported. The proportion of RV identified in healthy subjects is significantly lower than in CAP, but it is not zero and should be weighed when interpreting corresponding proportions among patients.